2022
DOI: 10.1186/s12879-022-07381-8
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of metagenomic next-generation sequencing of bronchoalveolar lavage fluid for the diagnosis of suspected pneumonia in immunocompromised patients

Abstract: Background To evaluate the diagnostic value of metagenomic next-generation sequencing (mNGS) of bronchoalveolar lavage fluid (BALF) in immunocompromised patients for the diagnosis of suspected pneumonia in comparison with that of conventional microbiological tests (CMTs). Methods Sixty-nine immunocompromised patients with suspected pneumonia received both CMTs and mNGS of BALF were analyzed retrospectively. The diagnostic value was compared between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 30 publications
4
18
0
Order By: Relevance
“…In our study, it has been possible to lyse Aspergillus and extract the relevant DNA for amplification detection well, benefiting from the development of pretreatment techniques for mNGS. A related study by Lin et al, which included 69 immunodeficient patients with suspected pneumonia, concluded in agreement with us that the diagnostic efficacy of mNGS was significantly better than that of CMTs (Lin et al, 2022). Both studies by Peng et al and Lin et al compared the sensitivity and specificity of the two methods through simple statistical calculations, without using statistical tools such as ROC curves to comprehensively analyze the difference in diagnostic efficacy between mNGS and CMTs, and did not give diagnostic cutoff values.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In our study, it has been possible to lyse Aspergillus and extract the relevant DNA for amplification detection well, benefiting from the development of pretreatment techniques for mNGS. A related study by Lin et al, which included 69 immunodeficient patients with suspected pneumonia, concluded in agreement with us that the diagnostic efficacy of mNGS was significantly better than that of CMTs (Lin et al, 2022). Both studies by Peng et al and Lin et al compared the sensitivity and specificity of the two methods through simple statistical calculations, without using statistical tools such as ROC curves to comprehensively analyze the difference in diagnostic efficacy between mNGS and CMTs, and did not give diagnostic cutoff values.…”
Section: Discussionsupporting
confidence: 83%
“…In our study, it has been possible to lyse Aspergillus and extract the relevant DNA for amplification detection well, benefiting from the development of pre-treatment techniques for mNGS. A related study by Lin et al., which included 69 immunodeficient patients with suspected pneumonia, concluded in agreement with us that the diagnostic efficacy of mNGS was significantly better than that of CMTs ( Lin et al., 2022 ). Both studies by Peng et al.…”
Section: Discussionsupporting
confidence: 79%
“…In fact, nowadays, PCP has a fair proportion in the non-HIV immunocompromised children. The rapid detection of pathogens by mNGS is conducive to the timely diagnosis and treatment of critically pediatric patients [33][34][35]. In this retrospective study of 17 PCP critically pediatric patients, the dominant underlying conditions included hematologic malignancies, solid tumors, and rheumatic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, our study was not further validated using Gomori methenamine silver staining, which may have influenced the comparison of the two testing methods. Recent studies ( Wang et al., 2019b ; Lin et al., 2022 ) have shown that mNGS has good diagnostic performance in the detection of pneumocystis. The identification of Aspergillus spp.…”
Section: Discussionmentioning
confidence: 99%